Construction and application of "organ-system-centered" undergraduate nursing professional training model - Yuqing Li; Lei-lei Guo; Jiaofeng Gui; Xiaoyun Zhang; Ying Wang; Haiyang Liu; Jinlong Li; Yunxiao Lei; Xiaoping Li; Lu Sun; Liu Yang; Ting Yuan; et al. (BMC, 2024)
Abstract Objective The purpose of this study is to construct an organ system-centered undergraduate nursing professional training model and explore its application effect. Methods This study is divided into two steps. In the early stage, literature review and expert consultation were used to establish the training mode (curriculum and assessment standard) of nursing undergraduate specialty based on organ system reform. Secondly, a cross-sectional survey method was used to investigate the training quality of nursing students who graduated from Jinzhou Medical University from 2007 to 2017 under this model. Results A five-module curriculum system was established, including general courses, public basic courses, professional education courses, expanding elective courses and concentrated practical teaching. Under the teaching reform of organ system, the nursing graduates of Jinzhou Medical University, who are mainly employed in public hospitals, are generally not satisfied with their jobs, salaries, contents and prospects. Their overall satisfaction with their alma mater is very high; Graduates have certain independent core competence; Employers are basically satisfied with graduates. Conclusion The training mode of undergraduate nursing specialty based on organ system reform basically meets the training requirements and objectives.